Power over and power with: integrating the concept of power into design team and stakeholder interactions - Schimpf, Corey; Swenson, Jessica; Burris, Courtney (Frontiers in Education, 2024)
As professionals in the workplace, engineers often have high levels of power or social influence over other people or groups they work with, including in decision-making, project planning, and other professional activities. The concept of power has received considerable attention in the social sciences and humanities but has received less attention in engineering education. Despite this, power is a crucial topic for engineers to understand as they are constantly navigating power dynamics across many groups of stakeholders. In this space we introduce the concepts of power over and power with into a two-semester senior engineering design capstone course through a series of activities and project scaffolds. Briefly, power over involves an actor being able to constrain the actions of another whereas power with involves an actor being able to empower or enable another actor to take new actions. Students were taught a framework that combines the concepts of power over and power with to reconsider and transform their interactions with stakeholders. We employ a case study to show how these concepts were integrated into the class and use directed content analysis of students’ final design reports to analyze the degree to which students were able to apply this framework. The results first highlight how activities over the semesters helped students learn the framework and later apply them. Next, the results of content analysis indicate that students were able to share power with several stakeholders and recognize some instances or risks of power over, although some gaps remained with how power was reported or recognized. This work extends and adapts concepts of power from the social sciences and humanities to the field of engineering education, argues for the importance of covering both power over and power with in classes and provides some evidence of the productive beginnings of engineering students using these concepts. We close with implications for other engineering classes and future research.